2018
DOI: 10.1186/s41936-018-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the occurrence of nonylphenol in the marine environments, Chennai—a case study

Abstract: Background: Resisting degradation, nonylphenol (NP) remains as a critical compound contaminating many habitats. Prevalence of nonylphenol in the ecosystem of Indian coastlines is not well documented as that of fresh water. Hence, the present study was intended to estimate the concentration of nonylphenol from water and sediments samples of Chennai (Madras) coastline which is polluted with anthropogenic activities from the city. Results: Six stations were sampled such as Ennore mouth, Ennore creek, Kasimedu, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a previous study based in China, measurements of NPs in sediment were more than one thousand times higher than measurements of NPs in water streams (Xu et al, 2006). Likewise, in a more recent study of the Chennai (Madras) coastline measurements of NPs were found to be higher in sediment samples than water samples (Raju et al, 2018).…”
Section: Levels Of Nonylphenolsmentioning
confidence: 75%
See 1 more Smart Citation
“…In a previous study based in China, measurements of NPs in sediment were more than one thousand times higher than measurements of NPs in water streams (Xu et al, 2006). Likewise, in a more recent study of the Chennai (Madras) coastline measurements of NPs were found to be higher in sediment samples than water samples (Raju et al, 2018).…”
Section: Levels Of Nonylphenolsmentioning
confidence: 75%
“…, 2006). Likewise, in a more recent study of the Chennai (Madras) coastline measurements of NPs were found to be higher in sediment samples than water samples (Raju et al. , 2018).…”
Section: Discussionmentioning
confidence: 89%
“…2 However, the nonylphenol concen-trations of 1.22 to 7.24 μg/L, 3.31 to 30.96 μg/kg, and 18.03 to 23.89 mg/kg have been recorded in water, sediments, and tomato plant, respectively. 3,4 Living organisms are exposed to nonylphenol throughout their lives via the ingestion of contaminated food/water, causing a disturbance in hormonal balance and consequently leading to various health disorders such as behavior disorders, developmental and reproductive abnormalities, and alterations in immune functions. [5][6][7] In a study by Paolella et al, 8 nonylphenol exposure causes ER stress, apoptosis, and mitochondrial dysfunction in the hepatic cell line.…”
Section: Introductionmentioning
confidence: 99%